Melatonin inhibits the migration of human gastric carcinoma cells at least in part by remodeling tight junction. Issue 6 (9th December 2018) - Wei, Xiang; Chen, Shaolong; Xu, Zhe; Jia, Ning; Qi, Yinliang; Zhou, Qing; Wang, Jian; Qu, Lijun; Zhang, Sumei; Wang, Yuan
Abstract: The recurrence and metastasis is one of the major reasons for malignant tumor treatment failure. Melatonin, a naturally occuring hormone, could reduce the recurrence and metastasis of various tumors. However, the underlying molecular mechanisms of melatonin on tumor metastasis inhibition have not been fully elucidated. In the present study, we explored the impact of melatonin on the migratory capability of human gastric carcinoma cells using wound healing assay, and further investigated if the inhibition on migration ability of melatonin was embodied by relocating tight junction proteins zo‐1 and occludin onto the cells surface to remodel tight junction structure. Immunofluorescence assay and Western blot analysis were performed to detect the expression and cell location of the tight junction proteins. The migration distance was decreased as the cells were treated with melatonin. And melatonin increased the membrane location of tight junction proteins, zo‐1 and occludin, showed by immunofluorescence staining and Western blot analysis. The results we got show that melatonin makes tight junction proteins anchored more on the cells membrane to remodel cells tight junction, which increase cells adhesion and decrease motility, resulting in the inhibition of gastric cancer cells migration and metastasis ability. Abstract : The recurrence and metastasis is one of the major reasons for malignant tumor treatment failure. Melatonin, a naturally occuring hormone, could reduce the recurrence and metastasis of various tumors. In the present study, we explored the impact of melatonin on the migratory capability of human gastric carcinoma cells and investigated its molecular mechanisms.